Biofortification and its Impact on Human Health - Kundu, Santanu; Pooniya, Vijay; Kasbe, Sudhanshu Sudhakar; Likhitha, A.; Saikia, Nilutpal; Barman, Anamika; Shah, Maksud Hasan; Ramanjaneyulu, A. V.; Kumar, S. Vijay (Chronicle of Bioresource Management, 2025)
India accounts for 17.7% of the world population and holds 1st position in the world. Despite having huge population pressure, India is now self-sufficient in food production. Human resource is the most important wealth of a country. However, a large number of Indian people are suffering from malnutrition owing to nutritional insufficiency in staple food. Malnutrition and impaired human health are one of the major obstacles for country’s development, and monetary loss pertaining to malnutrition is US12 billion GDP year-1. There are different approaches to increase the quality of food with essential compounds and biofortification is one of the cheapest methods to alleviate this problem. Agronomic biofortification deals with external growth factors while genetic biofortification deals with plant genetic character for higher acquisition and synthesis of essential elements and their remobilization in plant’s edible part. In this article, an insight was given on the significance of biofortification in India, different methods of biofortifications and its impact on human health.